2022
DOI: 10.31557/apjcp.2022.23.10.3317
|View full text |Cite
|
Sign up to set email alerts
|

Study on Preoperative Neutrophil/Lymphocyte (NLR) and Platelet/Lymphocyte Ratio (PLR) as a Predictive Factor in Endometrial Cancer

Abstract: Objective: To evaluate predictive factors between serum inflammatory markers and malignancy potential of endometrium. Methods: This retrospective study was conducted at the gynecological oncology unit, department of obstetrics and gynecology, at the faculty of medicine of Thammasat University. The study period was from 2017 to 2020. Endometrial cancer and benign gynecologic disease cases who underwent hysterectomy (with or without adnexectomy) during the study period were recruited. Demographic characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…PLR is the ratio of platelet to lymphocyte. It was not only associated with the outcome of many tumor patients, but also associated with the response of tumor patients to anti-tumor therapy ( 10 , 11 ). Among patients with acute ischemic stroke, higher PLR was possibly associated with poor outcome, reperfusion insufficiency, and infarct size ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…PLR is the ratio of platelet to lymphocyte. It was not only associated with the outcome of many tumor patients, but also associated with the response of tumor patients to anti-tumor therapy ( 10 , 11 ). Among patients with acute ischemic stroke, higher PLR was possibly associated with poor outcome, reperfusion insufficiency, and infarct size ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In endometrial cancer patients, PLR ≥ 134.95 was associated with invasion of myometrium ≥50%. [ 19 ] In advanced non-small cell lung cancer patients, higher PLR level was an independent risk factor associated with the first-line chemotherapy efficacy and clinical prognosis. [ 20 ] In addition to tumors, the results of other studies also confirmed the association between PLR level and infection.…”
Section: Discussionmentioning
confidence: 99%
“…Whether PLR can be used to distinguish hyperplasia and cancer from pathologically normal patients remains controversial. However, a large number of studies have confirmed that PLR has a certain predictive value in the progression and prognosis of EC patients, and the increase of PLR is closely related to tumor staging, including muscle invasion, cervical involvement, lymph node involvement, lymphatic vascular space invasion and distant metastasis [5] .Although the available studies do not support the use of PLR in the diagnosis of EC, it appears to be associated with late and distant metastases and is a promising hematologic parameter for evaluating the prognosis of EC.…”
Section: Platelet-to-lymphocyte Ratio (Plr)mentioning
confidence: 99%